Political economics, collective action and wicked socio-ecological problems - Lisa Bernadette Adams, Ms; Theodore Roberts Alter, Professor; Margot Parkes, Professor; Andrew Woolnough, Dr; Michael Reid, Mr (Gateways, 2019)
Empowering integrative, sustainable and equitable approaches to wicked socio-ecological problems requires multiple disciplines and ways of knowing. Following calls for greater attention to political economics in this transdisciplinary work, we offer a practitioner perspective on political economy and collective action and their influences on our community engagement practice and public policy. Our perspective is grounded in a pervasive wicked problem in Australia, invasive rabbits, and the emergence of the Victorian Rabbit Action Network. The network grew out of a publically funded research project to support community-led action in rabbit management. Victorian residents and workers affected by rabbits – public and private land managers, scientists, government officers and others – were invited to engage in a participatory planning process to generate sustainable strategies to address the rabbit problem. Each stage in the process, which involved interviews, a workshop and consultations, was designed to nurture the critical enquiry, listening and learning skills of participants, advance understandings of the problem from multiple perspectives, generate collective options to guide decision-making, and encourage community-led collective action. We reflect on our understanding of these processes using the language and lens of political economics, and in particular, the context of democratic professionalism. In so doing, we define terms and refer to information resources that have enabled us to bring a practical working knowledge of political economics to our professional practice. Our intent is to motivate academics, community members, government officials, and scientists alike, to draw on their knowledge and field experiences and to share practice stories through the lens of political economics and collective action. The opportunity is to engage each other in small ‘p’ politics of how we understand and act on wicked problems: to negotiate and connect across disciplines, practical experiences, and human difference, so that people may work more creatively and effectively together to address the challenging issues of our time.